High-entropy hydrogen storage alloy and preparation method thereof

By adopting the high-entropy hydrogen storage alloy with the chemical formula of V30-xTiyCrzAlrMt(FeV)x, combined with the smelting and heat treatment technology of vacuum induction furnace, the hydrogen absorption/discharge capacity and cycle life of the high-entropy V-based alloy is solved, and efficient hydrogen storage and release is achieved.

CN119956189AActive Publication Date: 2025-05-09DALIAN UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510337778.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-05-09
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to provide high entropy V-based alloys, and the alloy's hydrogen absorption/discharge capacity, hydrogen absorption and discharge power and cycle life are poor.

Method used

The chemical formula of V30-xTiyCrzAlrMt(FeV)x is used, and smelting and heat treatment is carried out through a vacuum induction furnace, and elements such as ferrovana vanadium ferroalloy FeV80 and zirconium or cerium are added to form a high-entropy hydrogen storage alloy.

Benefits of technology

It achieves high hydrogen absorption capacity and wide temperature zone adaptability under cost controllable and industrial-grade smelting conditions, which is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119956189A_ABST
    Figure CN119956189A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen storage materials, in particular to a high-entropy hydrogen storage alloy which is characterized in that the chemical formula of the alloy is V30-xTiyCrzAlrMt (FeV) x, FeV is ferrovanadium alloy FeV80, M is at least one of Zr or Ce, x, y, z, r and t are the atomic percent of V, Ti, Cr, Al, M and FeV respectively, x + y + r + t = 100, 0 < = x < = 30, 20 < = y < = 30, 20 < = z < = 30, 5 < = r < = 10, 5 < = t < = 10, the alloy is the high-entropy hydrogen storage alloy with a BCC structure, and the alloy has a BCC structure. The material has excellent hydrogen absorption / desorption capacity, excellent hydrogen absorption / desorption power and long cycle life, and is suitable for industrial large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen storage materials, and in particular relates to a high entropy hydrogen storage alloy and a preparation method thereof. Background Art

[0002] Hydrogen energy, due to its renewability and cleanliness, has become an ideal choice to meet energy needs and solve environmental problems. Efficient hydrogen storage technology is the key to promoting the development of the hydrogen economy. Hydrogen storage technology is divided into three types: gaseous hydrogen storage, liquid hydrogen storage and solid hydrogen storage. Among them, the equipment of high-pressure gaseous hydrogen storage technology is the most complete, but the hydrogen storage capacity is small and the safety is poor. Low-temperature liquid hydrogen storage can greatly improve the volume capacity, but hydrogen liquefaction is very energy-consuming. Liquid hydrogen storage requires special containers that can withstand ultra-low temperatures, maintain ultra-low temperatures, withstand pressure, and have strong sealing. The manufacturing is difficult and the cost is high. Solid-state storage and transportation uses metal hydrides, chemical hydrides or nanomaterials as hydrogen storage carriers. Among them, metal hydride hydrogen storage technology has attracted much attention due to its high volume hydrogen storage capacity, good cycle stability, high hydrogen supply purity and excellent safety.

[0003] Among all metal hydride hydrogen storage materials, vanadium (V) based solid solution hydrogen storage alloys with body-centered cubic structure have attracted much attention due to their good kinetics, high hydrogen storage capacity (theoretical maximum capacity 3.9wt%) and moderate working conditions. In recent years, the research on V-based BCC alloys has mainly focused on the V-Ti-X alloy system (X = Cr, Fe, Ni, Zr, Mn, etc.), among which V-Ti-Cr system alloys are the focus of various studies due to their good hydrogen storage performance. V is a necessary element to stabilize the BCC structure and increase the hydrogen pressure. However, due to the high cost of pure V alloys, high V alloys are not suitable for the production of hydrogen. The high cost of gold poses a major obstacle to large-scale applications. Therefore, the development of BCC alloys containing low V is of great value. In addition, based on cost considerations, compared with pure vanadium, cheap ferrovanadium alloy (FeV80) is more suitable as a raw material for vanadium-based solid solution hydrogen storage alloys. The V-Ti-Cr system alloy using ferrovanadium alloy is very suitable for adding other elements to obtain cheap high-entropy hydrogen storage alloys, which has great development potential. Compared with traditional vanadium-based hydrogen storage alloys, high-entropy vanadium-based hydrogen storage alloys can achieve a larger hydrogen storage capacity, better stability, better cycle life performance, and lower hydrogen desorption temperature.

[0004] Therefore, there is an urgent need to solve the technical problem of how to provide a high-entropy V-based alloy with excellent hydrogen absorption / desorption capacity, hydrogen absorption and desorption power, and cycle life. Summary of the invention

[0005] The present invention aims to solve the technical problem of how to provide a high entropy V-based alloy with excellent hydrogen absorption / desorption capacity, hydrogen absorption and desorption power and cycle life.

[0006] In order to achieve the above object, the present invention provides a high entropy hydrogen storage alloy in a first aspect, wherein the chemical formula of the alloy is V 30-x Ti y Cr z Al r M t (FeV) x , wherein FeV is vanadium-iron alloy FeV80, M is at least one of Zr or Ce, x, y, z, r, t are the atomic percentages of V, Ti, Cr, Al, M, and FeV, respectively, x+y+z+r+t=100, 0≤x≤30, 20≤y≤30, 20≤z≤30, 5≤r≤10, 5≤t≤10.

[0007] A second aspect of the present invention provides a method for preparing the alloy according to any one of claims 1 to 4, wherein the preparation method comprises:

[0008] S1. According to the atomic ratio, the mixed raw materials are placed in the crucible of a vacuum induction furnace, and vacuumed, heated and degassed;

[0009] S2, using a vacuum induction furnace, evacuating the vacuum and filling it with argon protection, heating to 1800-1900°C, maintaining for 3-5 minutes, continuously shaking the crucible to accelerate dissolution, tilting the crucible, and quickly pouring the alloy into a water-cooled crucible at a cooling rate of 800-1200°C / min, cooling to 20-30°C, and obtaining an alloy ingot;

[0010] S3, heating up to 1200°C in stages, heat treatment for 15-30 min, N2 gas quenching, sandpaper grinding to remove the oxide layer on the surface of the alloy ingot after gas quenching, liquid nitrogen treatment, crushing, and obtaining the alloy.

[0011] The beneficial effect of the present invention is that the alloy provided by the present invention has a very high hydrogen absorption capacity and excellent adaptability in a wide temperature range of -30°C to 250°C under cost-controllable and industrial-grade smelting conditions, and is very suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 X-ray diffraction patterns of single-phase BCC V-Ti-Cr-Fe-Zr-Al and V-Ti-Cr-Fe-Ce-Al based high entropy hydrogen storage alloys prepared in Examples 1 and 2;

[0013] Figure 2 The PCT curve diagram of the single-phase BCC V-Ti-Cr-Fe-Zr-Al based high entropy hydrogen storage alloy prepared in Example 1;

[0014] Figure 3 The hydrogen absorption kinetics curve of the single-phase BCC V-Ti-Cr-Fe-Zr-Al based high entropy hydrogen storage alloy prepared in Example 1;

[0015] Figure 4 This is a hydrogen desorption kinetics curve of the single-phase BCC V-Ti-Cr-Fe-Zr-Al based high entropy hydrogen storage alloy prepared in Example 1. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The first aspect of the present invention provides a high entropy hydrogen storage alloy, wherein the chemical formula of the alloy is V 30- x Ti y Cr z Al r M t (FeV) x , wherein FeV is vanadium-iron alloy FeV80, M is at least one of Zr or Ce, x, y, z, r, t are the atomic percentages of V, Ti, Cr, Al, M, and FeV, respectively, x+y+z+r+t=100, 0≤x≤30, 20≤y≤30, 20≤z≤30, 5≤r≤10, 5≤t≤10.

[0018] In the present invention, the chemical elements and proportions of the alloy are of specific composition and proportion. Vanadium is the main forming element of the body-centered cubic (BCC) structure, providing high-density interstitial sites (tetrahedral and octahedral sites), and the theoretical hydrogen storage capacity can reach more than 4wt.%, but pure vanadium is easy to form stable hydrides (such as VH2), resulting in excessively high hydrogen release temperature (>200°C). The atomic radius of titanium is larger than that of vanadium, and after solid solution, the BCC lattice gap is enlarged, the hydrogen embedding energy barrier is reduced, and the hydrogen storage capacity is increased. In addition, titanium reduces the formation enthalpy of hydrides, so that the dehydrogenation temperature is reduced. Chromium promotes the dissociation and recombination of hydrogen molecules (H2) on the alloy surface, accelerates the kinetics of hydrogen absorption and dehydrogenation reactions, and the Cr2O3 passivation film inhibits alloy oxidation, improves cycle stability, and iron, as an element introduced into the vanadium-iron alloy, reduces material costs. Aluminum reduces the thermal stability of hydrides, making it easier to dehydrogenate at low temperatures. The addition of zirconium induces the formation of nanocrystalline or amorphous phases, increases the density of grain boundaries, and provides a fast hydrogen diffusion channel. The atomic radius of cerium is significantly larger than that of vanadium. Its solid solution into the BCC lattice will cause lattice expansion and local distortion, increase the volume of interstitial sites of hydrogen atoms, and reduce the hydrogen embedding energy barrier, thereby improving the effective hydrogen storage capacity. It is oxidized on the alloy surface to form CeO2 nanoparticles, which significantly promote the dissociation and recombination of hydrogen molecules (H2) and reduce the surface reaction activation energy. The alloy of the above elements under the specific ratio of the present invention has good hydrogen absorption and desorption capacity.

[0019] According to the present invention, 90-100% of the alloy crystal forms are body-centered cubic structures.

[0020] According to the present invention, the activation method of the alloy is:

[0021] After vacuuming at 400°C for 240 minutes, 4-10 MPa of H2 was charged, and hydrogen was absorbed and released once. The hydrogen absorption condition was to keep the temperature at 400°C for 240 minutes and then naturally cool to 20-30°C.

[0022] or;

[0023] After evacuating at 180°C for 240 minutes, 4-10 MPa of H2 was charged, and hydrogen was absorbed and released three times. The hydrogen absorption condition was to keep the temperature at 180°C for 240 minutes and then naturally cool to 20-30°C.

[0024] According to the present invention, under the conditions of 25° C. and 8-10 MPa of H 2 , the maximum hydrogen absorption capacity of the alloy is 2.73 wt %.

[0025] According to the present invention, at -30°C, the maximum hydrogen absorption capacity of the alloy is 2.8wt%, and at 150-250°C, the 2.8wt% hydrogen storage capacity can be completely released.

[0026] In the present invention, the alloy is suitable for cold regions or extreme aerospace environments, and the hydrogen desorption temperature range is perfectly matched with the industrial waste heat temperature (such as 200-400°C waste heat from steel mills and 150-250°C reaction heat from chemical plants), without the need for additional heating energy consumption.

[0027] A second aspect of the present invention provides a method for preparing the alloy according to any one of claims 1 to 4, wherein the preparation method comprises:

[0028] S1. According to the atomic ratio, the mixed raw materials are placed in the crucible of a vacuum induction furnace, and vacuumed, heated and degassed;

[0029] S2, using a vacuum induction furnace, evacuating the vacuum and filling it with argon protection, heating to 1800-1900°C, maintaining for 3-5 minutes, continuously shaking the crucible to accelerate dissolution, tilting the crucible, and quickly pouring the alloy into a water-cooled crucible at a cooling rate of 800-1200°C / min, cooling to 20-30°C, and obtaining an alloy ingot;

[0030] S3, heating up to 1200°C in stages, heat treatment for 15-30 min, N2 gas quenching, sandpaper grinding to remove the oxide layer on the surface of the alloy ingot after gas quenching, liquid nitrogen treatment, crushing, and obtaining the alloy.

[0031] According to the present invention, the raw materials include V, Ti, Cr, Al, FeV80, and M, where M is at least one of Zr and Ce.

[0032] According to the present invention, V, Ti, Cr, Fe and M are first placed at the bottom of a crucible of a vacuum induction furnace, Al and Fe80V are added last, and M is at least one of Zr and Ce.

[0033] In the present invention, the placement of the metals described above can reduce oxidation and volatilization.

[0034] In the present invention, the melting point of V is not higher than 1890° C., but the V content of the alloy of the present invention is low, and the V in the alloy can be partially melted by induction eddy current.

[0035] According to the present invention, in S1, the heating and degassing conditions include: using a vacuum pump to evacuate, heating at a rate of 10-20°C / min, heating to 500-800°C, and maintaining for 0.5-1h.

[0036] According to the present invention, in S3, the conditions for staged heating include: heating to 700-900°C at a rate of 5-10°C / min, and then heating to 1100-1200°C at a rate of 1-3°C / min.

[0037] According to the present invention, in S3, the conditions of N2 gas quenching include: N2 pressure of 5-15 bar, gas flow rate of 5-15 m / s, and ventilation time of 10-15 min.

[0038] According to the present invention, in S3, the liquid nitrogen treatment is to place the polished alloy ingot into liquid nitrogen, cool it to -170 to (-190)°C, and keep it for 10 to 30 minutes.

[0039] In the present invention, due to the high vanadium and chromium content, the hardness and toughness of the cast alloy block are extremely high and it is difficult to crush it into the required alloy powder. Therefore, liquid nitrogen treatment is used to reduce the toughness of the alloy block and induce the microscopic defects in the material to amplify and form cracks, so that it is broken into small pieces. The small pieces of alloy are then vibrated into powder, which can be directly used for hydrogen storage.

[0040] Test Method

[0041] The hydrogen storage properties of the alloys were determined by Sievert ’ Measured by s method.

[0042] The technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the embodiments described herein are only some embodiments of the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments implemented by ordinary technicians in this field without making creative improvements belong to the protection scope of the present invention.

[0043] Example 1

[0044] S1. According to chemical composition V 30 Ti 25 Cr 25 Fe5Zr5Al 10 During the smelting process, the vacuum induction furnace is first evacuated and the temperature is raised to 800°C at 10°C / min, and then kept at this temperature for 1 hour to remove the impurity gases adsorbed on the raw materials;

[0045] S2, using a vacuum induction furnace, evacuating the vacuum and filling it with argon protection, heating to 1900°C for 5 minutes and continuously shaking the crucible to accelerate dissolution, tilting the crucible, and quickly pouring the alloy into a water-cooled crucible at a cooling rate of about 500°C / min, cooling to 25°C to obtain an alloy ingot;

[0046] S3. Place the alloy ingot in a quartz tube, heat it from room temperature to 800°C at a rate of 5°C / min, then heat it to 1200°C at a rate of 1°C / min, and keep it warm for 15 minutes. After the insulation is completed, take out the quartz tube containing the sample at 1400°C, quench it with 10 bar N2 gas, polish the oxide layer on the surface of the alloy block with sandpaper, cool it to -190°C with liquid nitrogen, keep it for 30 minutes, and crush it to obtain alloy A1.

[0047] Example 2

[0048] According to the preparation method of Example 1, the difference is that according to the chemical composition V 30 Ti 25 Cr 25 Fe5Ce5Al 10 The ingredients were mixed to obtain alloy A2.

[0049] Example 3

[0050] The preparation method of Example 1 was followed, except that the temperature of the liquid nitrogen was lowered to -170°C to obtain alloy A3.

[0051] Example 4

[0052] The preparation method of Example 1 was followed, except that the liquid nitrogen was cooled to -180°C to obtain alloy A4.

[0053] Example 5

[0054] Alloy A5 was obtained by following the preparation method of Example 1, except that the liquid nitrogen cooling holding time was 10 min.

[0055] Example 6

[0056] Alloy A6 was obtained by following the preparation method of Example 1, except that the liquid nitrogen cooling holding time was 20 minutes.

[0057] Comparative Example 1

[0058] According to the preparation method of Example 1, the difference is that according to the chemical composition V 30 Ti 25 Cr 25 Fe8Zr5Al 12 The ingredients were mixed to obtain alloy DA1.

[0059] Comparative Example 2

[0060] Alloy DA2 was obtained by following the preparation method of Example 1 except that no liquid nitrogen treatment was performed.

[0061] XRD analysis of alloys A1-A5 showed that the alloys were mainly of BCC structure.

[0062] The alloy A1 prepared in Example 1 has a hydrogen storage capacity of 2.73 wt % at 25° C., a hydrogen release capacity of 0.8 wt %, and an effective hydrogen storage capacity of 2.03 wt %.

[0063] The alloy A2 prepared in Example 2 has a hydrogen storage capacity of 2.83 wt% at 25°C and a hydrogen release capacity of 0.92 wt%.

[0064] The alloy DA1 prepared in Comparative Example 1 has a hydrogen storage capacity of 1.84wt% and a hydrogen release capacity of 1.1wt%, indicating that excessive content of vanadium iron ore and aluminum leads to the formation of too many impurities, which reduces the hydrogen absorption capacity of the alloy.

[0065] Instructions attached Figure 3 and 4 It shows that the alloy A1 prepared in Example 1 has good hydrogen absorption and desorption kinetics.

[0066] By comparing Example 1 and Examples 3-6 with Comparative Example 2, it can be seen that the method for preparing the alloy provided in the present application uses liquid nitrogen treatment before crushing to obtain alloy powder that can be used in hydrogen storage.

[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high entropy hydrogen storage alloy, characterized in that: The chemical formula of the alloy is V 30-x Ti y Cr z Al r M t (FeV) x , wherein FeV is vanadium-iron alloy FeV80, M is at least one of Zr or Ce, x, y, z, r, t are the atomic percentages of V, Ti, Cr, Al, M, and FeV, respectively, x+y+z+r+t=100, 0≤x≤30, 20≤y≤30, 20≤z≤30, 5≤r≤10, 5≤t≤10.

2. The alloy according to claim 1, characterized in that Among the crystal forms of the alloy, 90-100% is a body-centered cubic structure.

3. The alloy according to claim 1, characterized in that The activation method of the alloy is: After vacuuming at 400°C for 240 minutes, 4-10 MPa of H2 was charged, and hydrogen was absorbed and released once. The hydrogen absorption condition was to keep the temperature at 400°C for 240 minutes and then naturally cool to 20-30°C. or; After evacuating at 180°C for 240 minutes, 4-10 MPa of H2 was charged, and hydrogen was absorbed and released three times. The hydrogen absorption condition was to keep the temperature at 180°C for 240 minutes and then naturally cool to 20-30°C.

4. The alloy according to claim 1, characterized in that At 25°C and 8-10MPa of H2, the maximum hydrogen absorption capacity of the alloy is 2.73wt%; At -30°C, the maximum hydrogen absorption capacity of the alloy is 2.8wt%, and at 150-250°C, the 2.8wt% hydrogen storage capacity can be completely released.

5. A method for preparing the alloy according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1. According to the atomic ratio, the mixed raw materials are placed in the crucible of a vacuum induction furnace, and vacuumed, heated and degassed; S2, using a vacuum induction furnace, evacuating the vacuum and filling it with argon protection, heating to 1800-1900°C, maintaining for 3-5 minutes, continuously shaking the crucible to accelerate dissolution, tilting the crucible, and quickly pouring the alloy into a water-cooled crucible at a cooling rate of 800-1200°C / min, cooling to 20-30°C, and obtaining an alloy ingot; S3, heating up to 1200°C in stages, heat treatment for 15-30 min, N2 gas quenching, sandpaper grinding to remove the oxide layer on the surface of the alloy ingot after gas quenching, liquid nitrogen treatment, crushing, and obtaining the alloy.

6. The method according to claim 5, characterized in that The raw materials include V, Ti, Cr, Al, FeV80, and M, where M is at least one of Zr and Ce; V, Ti, Cr, Fe and M are first placed at the bottom of a crucible in a vacuum induction furnace, and Al and Fe80V are added last, wherein M is at least one of Zr and Ce.

7. The method according to claim 5, characterized in that In S1, the heating degassing conditions include: using a vacuum pump to evacuate, heating at a rate of 10-20°C / min, heating to 500-800°C, and maintaining for 0.5-1h.

8. The method according to claim 5, characterized in that In S3, the conditions for staged temperature increase include: increasing the temperature to 700-900°C at a rate of 5-10°C / min, and then increasing the temperature to 1100-1200°C at a rate of 1-3°C / min.

9. The method according to claim 5, characterized in that In S3, the conditions of N2 gas quenching include: N2 pressure of 5-15 bar, gas flow rate of 5-15 m / s, and ventilation time of 10-15 min.

10. The method according to claim 5, characterized in that In S3, the liquid nitrogen treatment is to place the polished alloy ingot into liquid nitrogen, cool it to -170 to (-190)°C, and keep it for 10 to 30 minutes.

Citation Information

Patent Citations

  • High capacity vanadium hydrogen occluding alloy produced with intermediate alloy FeV80

    CN101153362A

  • High-vanadium solid solution type hydrogen storage alloy and preparation method thereof

    CN115612903A

  • Vanadium alloy and preparation and application thereof

    CN117684063A

  • High-capacity hydrogen storage alloy and preparation method thereof

    CN119571135A

  • Ti-cr-v-fe hydrogen storage alloy

    KR100846235B1